Factors Determinant Islamic Financial Literacy among Students - Mohamad Azmi Abdullah; Siti Nur Aqilah Ab Wahab; Salehudin Sabar Falah Abu (2017)
This article iswritten to provide a deliberation reviews on the currentcontext of Islamic financial literacy among students. A research wasconducted through case studies carried out among the students ofUniversity Malaysia Sabah Campus W.P.Labuan and InstitutPendidikanGuru (IPG), KampusBatuLintang, Sarawak, a teacher training institute.The respondents are candidates to become teachers upon completingtheirstudies. Being knowledgeable and having skill in financial literacy,especially with respect to Islamic financial products, would be a greatasset to them. Based on current scenario, financial literacy in Islamicfinancial products should be enhanced, especially to the academicians.The findings from this research is expected to be able to determine thefactors influencing Islamic financial literacy among the students. Thisstudy employs a quantitative method using questionnaires distribution foranalysis puposes. Data are collected through a survey using a closedended questionnaire. Overall, the objective of this study is to determinethe determinant factors towards Islamic financial literacy among students.The implications and recommendations areprovided.